In-Hospital Stroke in a Multidisciplinary Hospital - S. S. Petrikov; G. R. Ramazanov; S. B. Binnatova; M. V. Tikhomirova (Неотложная медицинская помощь)
Introduction. Acute cerebrovascular event (ACVE) is the leading cause of persistent disability and death in the world. Due to the high medical and social significance, much attention is paid to the problem of out-of-hospital stroke, and the issues of diagnostics and treatment of in-hospital stroke are practically not studied.Relevance. In-hospital stroke is defined as stroke that develops in a patient hospitalized for other reasons. It is known that the incidence of in-hospital stroke ranges from 2 to 19% of all acute cerebrovascular accidents recorded in the hospital, 0.04–0.06% of all hospital admissions. It was found that patients with inhospital stroke have significant restrictions on thrombolytic therapy, mortality can reach 60%, and the diagnosis is often made with long delays and deviations in examination protocols. The most common pathogenetic subtype of in-hospital ischemic stroke is the cardioembolic subtype. The explanation for this is that in most cases, in-hospital ischemic strokes develop in patients after open cardiac surgery with prosthetics of one or more valves, bypass surgery in conditions of artificial circulation, carotid endarterectomy. In the overwhelming majority of patients, the first symptoms of in-hospital stroke are observed not by doctors, but by nurses, patients or their relatives. Mortality in in-hospital stroke is significantly higher than in non-hospital stroke, which is due to the high incidence of extracerebral complications in this cohort of patients, as well as initially more severe stroke.Aim of study. To analyze the incidence of in-hospital stroke and the tactics of its treatment in a multidisciplinary hospital.Material and methods. The study included 975 patients with ACVE hospitalized at the N.V. Sklifosovsky Research Institute for Emergency Medicine from January 1, 2018 to January 1, 2019. The inclusion criterion was any case of CVE - out-of-hospital or in-hospital. The study did not include patients with subarachnoid hemorrhage (SAH) where secondary cerebral ischemia developed against the background of vasospasm. Also, we did not include patients with stroke, transferred from other hospitals for neurosurgical treatment.Results. In total, in 2018 at the N.V. Sklifosovsky Institute ACVE were diagnosed in 975 patients, of which in-hospital and out-of-hospital strokes were diagnosed in 109 (11.2%) and 866 patients (88.8%), respectively. The proportion of in-hospital stroke was 0.03% of the total number of patients treated at the institute in 2018. Systemic thrombolytic therapy (sTLT) is the main method of treating patients with IS. However, patients with in-hospital stroke may have a large number of contraindications to this type of therapy. Systemic TLT was performed in 1 patient (1%) with in-hospital stroke, while in out-of-hospital stroke, thrombolysis was performed in 36 patients (4.7%). After analyzing the reasons for refusing to perform sLT in patients with in-hospital and out-of-hospital IS. The leading reason for the impossibility of sTLT in patients with in-hospital stroke was the unspecified time of disease development - 44 (43.2%). In 35 patients (34.3%) with in-hospital stroke, refusal to perform sLTT was associated with late IS diagnosis, despite the fact that the stroke developed in the hospital.Conclusion. Thus, an in-hospital stroke aggravates the course of the underlying disease and, as a consequence, the outcome of the disease, leads to an increase in social and medical and economic costs. In this regard, there is a need to study the prevalence, risk factors, clinical features of in-hospital stroke, as well as the development of diagnostic and therapeutic algorithms in order to improve the efficiency of care for patients with in-hospital stroke.